THEORIZING MIGRATION INFRASTRUCTURE IN LATIN AMERICA: THE CENTRAL ROLE OF MIDDLEMEN - Chan, Carol (Revista de Historia Social y de las Mentalidades, 2019)
This article takes as its starting point the observation that brokers have been overlooked in political and academic discussions about international migration in Latin America. Highlighting the historical role of brokers in global migration, this article challenges current scholarly emphasis on migrant agency and the role of the State in explaining regional migration. It does so by providing an overview of current research on migration infrastructure and arguing for its relevance to Latin America. Finally, diverse cases of Asian migration to Chile are described and analyzed as a way to highlight the political importance and relevance of the concept and the phenomenon of migration brokers.
Keywords: Migration; Infraestructure; Brokers; Asian Migration